Pengaruh Post Weld Heat TreatmentTerhadap Sifat Mekanis dan Korosi Sambungan Las Spiral Saw pada Pipa Baja ASTM A252 - Setiawan, Ipick; Noer Ilman, Mochammad (Jurnal Energi Dan Manufaktur, 2013)
Metal joint with welding system is increasingly used. i.e structure, piping or machine constuction. Some of the problems on welding is residual stress dan over hardness can decrease the weld toughness stress corrosion cracking. An effort to solve this problem is PWHT. PWHT has multiple functions, those are to reduces residual stress,increases ductility of HAZ and improves toughness in weld metal and HAZ regions.Heating process with various temperature is expected to make optimum PWHT temperature.This experiment was carried out to know the effect of PWHT torwad the toughness an corrosion of helical welding pipe ASTM A252. The welding process use SAW with groove double V, electrical current 375 A , voltage 35 V and heat input 2,8 kj/mm. Post weld heat treatment was carried out at various temperature 450oC, 550oC and 650oC during 3 hours followed by cooling process in furnace after that, these specimens ware tested the hardness, tensile strength, toughness and corrosion. The Result of research show that increasing of PWHT temperature, can increase the toughness and corrosion resistance of joint weldin, but the tensile strength is decreasre. The optimum PWHT temperature is 550o C with toughness 81 J at 0O C.
Keywords: corrosion, hardness, PWHT, SAW, tensile strength, toughness